The paratextual analysis of English translations of Arabic media narratives on Daesh - Hijjo, Nael F M; Surinderpal Kaur (Penerbit Universiti Kebangsaan Malaysia, 2017)
This paper investigates the role of media translations in reframing ‘reality’ and inserting ideologically-loaded concepts to promote certain agendas. It further examines the effectiveness of paratextual (re)framings as a strategic device in the manipulation of ‘reality’. It analyses the English translations of the Arabic media narratives on ‘Daesh’ employing the interdisciplinary approach of Baker (2006) narrative theory-informed. These English translations were published on the website of the Middle East Media Research Institute (MEMRI); a Washington-based think tank that is largely quoted by the Western, mainly the US, prominent media outlets. The data collected for the purpose of this study consists of 46 Arabic editorials alongside their 25 English translations. The findings of this research suggest that paratextual devices including titles, introductions, headings, images and their captions, and endnotes and glossaries are significant (re)framing tools that function outside the immediate text. MEMRI is found to successfully reframe the Arabic narratives on ‘Daesh’ in an attempt to sustain and further the meta-narrative of the ‘War on Terror’. The significance of this study is specifically to draw the awareness of the public of the different rival narratives circulated by the media.